Rapid Assessment of Socioeconomic Effect and Fear of COVID- 19 Lockdown in Mugu District of Nepal - Makai, Prabina; Baidya, Manish; Shrestha, Ganesh; Pohl, Gerda; Karki, Jiban; Atreya, Kishor (Journal of Karnali Academy of Health Sciences, 2020)
Background: COVID-19 pandemic has created unique crisis–psychological problems like fear and disruption in household economy. Poor households are particularly affected as their livelihoods are already fragile. Objective was to understand rural people’s perception, fear levels, and the associated behavioural and socio-economic impacts of the COVID-19 lockdown. Methods: The study rapidly interviewed 109 respondents from two rural municipalities in Mugu. Being rapid in design, this study interviewed those respondents (18 years or above providing consent) who visited one of the out-reach clinics for health care services. Data were collected through mobile and preventive measures were ensured during data collection process. This study is a sub-part of a research study in Mugu (Nepal Health Research Council Reg. no. 354/2020) as an immediate project management requirement for the same study in Mugu. Results: We did not find any gender wise differences in fear, both males and females were equally afraid of getting infected or dying from COVID-19. Almost all respondents had a mask, but there was a significant gap of 11% (P<0.05) in mask access when compared gender wise. The one-way ANOVA showed that people who were extremely afraid of the COVID-19 pandemic had higher percentage loss of household income (p<0.05). Conclusion: COVID-19 pandemic and the lockdown have intensified fear, reduced household earnings and economic activities, and disrupted access to markets and food consumption. Nevertheless, the preventive safe hygiene behaviours that are practiced during this pandemic shall be capitalized for sustainable better health effects.